Negative Status Condition - Hossein KAVIAR (مطالعات فقه و حقوق اسلامی)
The phrase “condition of non-performance" in Article 234 of the Civil Code gives rise to the assumption that the agreement to omission legal action is only with "condition of negative action". While, by induction in the civil law, there are instances that the convey of property or right is deprived from the owner or beneficiary without him committing to omission action.Articles 120, 448, 454, 460, 474, 500, 509, 679, 793 and 959 of the Civil Code are such. Deprivation of rights in these articles is subject to the generality of the conditions and in particular, subject to the condition of the result. Such condition is "negative status condition". The meaning of negative status condition is the condition that “Foreclosure " is created through its entry in the contract. In fact, “Foreclosure " is a direct and inherent effect of the negative status condition. This condition is subject to the existence of an objective or religious right. Despite the similarities between "negative status condition" and "negative status condition", But by providing criteria, it becomes possible to distinguish between these two conditions. One of the most important practical effects of the distinction between the negative status condition and the negative action condition is the guarantee execution of breach of condition. The result of the research shows that the guarantee execution of breach of condition of negative result is the invalidity of the opposite legal act, while the guarantee of the violation of the condition of the negative Status is the right of person in whose favor a condition is made termination.